Crystal structure and photoluminescence properties of CuBrxI1−x(melamine) (0 ≤ x ≤ 1) complexes - Kim, Juhyun; Kim, Donghyeon; Khefif, Fouzia; Yoon, Woojin; Yun, Hoseop; Yoo, Chung Yul; Kim, Seung Joo (Bulletin of the Korean Chemical Society, 2025)
Organic–inorganic copper(I) halide complexes have attracted attention due to their optoelectronic properties and non-toxic nature. In this study, we systematically synthesized copper(I) halide melamine complexes as single crystals, (CuBr(melamine) and CuI(melamine)) and polycrystalline powders, CuBrxI1-x(melamine) (0 ≤ x ≤ 1). The crystal structures of CuBr(melamine) and CuI(melamine) are isotypic with a triclinic space group P (Formula presented.), where copper(I) is connected with three adjacent halides along the a-axis and a single melamine ligand along the c-axis, forming an infinite stair-chain structure. The photoluminescence emission peaks of CuBrxI1-x(melamine) (0 ≤ x ≤ 1) show a red shift from 455 nm to 520 nm with the substitution of Br for I. This finding explains the structure–property relationship of organic–inorganic copper(I) halide complexes and provides guidelines for developing new organic–inorganic optoelectronic materials.
Keywords: Copper(I) halide; Crystals structures; Halide complexes; Inorganic complexes; Optoelectronic materials; Organic/inorganic; Organic–inorganic complex; Photoluminescence properties; Structure property; Structure-properties relationships; copper(I) halide; crystal structure; melamine; optoelectronic materials; organic–inorganic complexes; photoluminescence; structure–property relationship